The last stop - Mofokeng, Thabiso (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2016)
My novella is set in the taxi industry. Its main characters are a wealthy taxi owner, a poor taxi driver from another African country, and the taxi driver's girlfriend. The story is partly a ghost story and partly crime fiction, it combines gritty realism with magical elements. It shows what happens between people in times of taxi violence. As the plot develops, the driver finds out that his boss is sleeping with his girlfriend. In revenge, the boss bribes some policemen to arrest the driver and beat him, and he dies in the police cells. But it turns out that the detective investigating the driver's death is not quite impartial, nor is he of this world only.
Keywords: Uncatalogued